Plasma β-amyloid, tau, neurodegeneration biomarkers and inflammatory factors of probable Alzheimer’s disease dementia in Chinese individuals - Sun, Qingling; Ni, Jingnian; Wei, Mingqing; Long, Siwei; Li, Ting; Fan, Dongsheng; Lu, Tao; Shi, Jing; Tian, Jinzhou (Frontiers in Aging Neuroscience, 2022)
Background: Plasma-derived amyloid, tau, neurodegeneration (ATN) markers can accurately diagnose Alzheimer’s disease (AD) and predict its progression. Few studies have investigated the relationship between plasma biomarkers and changes in plasma inflammatory markers in clinically diagnosed AD. Methods: Seventy-four participants were recruited, including 30 mild-to-moderate AD dementia patients and 44 normal controls (NC). All participants underwent neuropsychological testing and blood sampling for biomarker testing. AD was clinically diagnosed according to the NIA-AA core criteria and required age-mismatched hippocampal atrophy. We performed Single Molecule Array, an ultra-sensitive enzyme-linked immunosorbent assay, to examine plasma ATN markers, including β-amyloid (Aβ) 40, Aβ42, p-tau181, total (t)-tau, neurofilament protein light chain (NfL), and inflammatory factors (TNF-α, IL-1β, IL-6, and IL-8). Results: The level of the plasma Aβ42/Aβ40 ratio was significantly declined and the levels of the plasma p-tau181, NfL and TNF-α were significantly higher in the AD group than the NC group, but there was no significant difference in the levels of plasma t-tau, IL-1β, IL-6 and IL-8 between the AD and NC groups. The levels of plasma p-tau181, NfL, Aβ42/Aβ40 ratio, and TNF-α were all associated with impairments in multiple cognitive domains. Among them, the plasma Aβ42/Aβ40 ratio, and the p-tau181 and TNF-α levels were associated with impairments in global cognition, memory, and visuospatial abilities, but not with executive function, only plasma NfL level was associated with executive function. Plasma NfL showed higher diagnostic performance in AD than in NC individuals (AUC=0.833). A combined diagnostic prediction model of plasma Aβ42/Aβ40 ratio, p-tau 181 and NfL had the highest value than each factor alone (AUC=0.902)，with a sensitivity and specificity of 0.867 and 0.886, respectively. Conclusions: The levels of plasma ATN biomarkers (Aβ42/Aβ40 ratio, p-tua181, NfL) were significantly changed in clinically diagnosed AD patients and they all associated with different domains of cognitive impairment. Plasma ATN biomarkers better differentiate mild-to-moderate AD dementia from NC when they are incorporated into diagnostic models together rather than individually. Plasma ATN biomarkers have the potential to be a screening tool for AD. However, the expression of inflammatory factors in AD patients requires further research.